Enhancing Flood Disaster Preparedness Through Virtual Reality: A VR-based Flood Simulator Game - Francisco Maruli Panggabean (Bina Nusantara University, 2023)
This research focuses on the use of virtual reality (VR) technology to increase user preparedness for flood disasters. This study aims to develop a VR-based flood simulation that provides users with immersive flood disaster simulations in line with flood preparedness guidelines. Game application needs are collected through questionnaires and similar application analysis. Evaluation is carried out to assess user needs, user interface (UI), and game effectiveness in increasing flood disaster preparedness. The evaluation was carried out by involving users who live in flood-prone areas, asking them to play a VR flood simulator game and filling out a questionnaire. The results show positive user perceptions and an average score increase of 25.38% in the second play session, indicating increased readiness. The VR flood simulator game shows its potential to increase preparedness and knowledge in dealing with flood disasters.